EDUKASI MASYARAKAT TENTANG PENERAPAN APD PADA PETUGAS POLI HIV DAN POLI TB DI PUSKESMAS KECAMATAN KLARI KABUPATEN KARAWANG - Widhiantika, Wieke; Darmawan, Wendi; Yuliana, Chaerani Tri; Jumaedi, Jumaedi; Muhidin, Muhidin (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The proper and consistent use of Personal Protective Equipment (PPE) in healthcare facilities is crucial, especially in high-risk units such as HIV and Tuberculosis (TB) clinics. This community service program aimed to improve the knowledge and compliance of healthcare workers in using PPE at the HIV and TB clinics at Puskesmas Kecamatan Klari, Karawang Regency, and to enhance public understanding of the importance of PPE in preventing the transmission of infectious diseases. The methods used included socialization and education sessions for healthcare workers and the public. The results of the program showed an increase in healthcare workers' knowledge from 60% before the education program to 90% afterward, and an improvement in compliance from 60% to 85%. Additionally, 85% of the public who participated in the education sessions reported a better understanding of the importance of PPE use. Therefore, this educational program proved effective in raising awareness and compliance with PPE usage among both healthcare workers and the public. Similar programs are recommended to be continued with the support of the Health Office to ensure consistent adherence to health protocols at Puskesmas